Islamic Communication Ethics in Response to the OnePiece Flag Polemic: Felix Siauw’s Content Analysis on Instagram Social Media - Hudin, Hafid; Ahmad Sopyan; Lukmanul Hakim; Mursam; Harjani Hefni; Maftuhah (Institut Studi Islam Muhammadiyah Pacitan, 2026)
This study examines the implementation of Islamic communication ethics in social media content, especially through the analysis of Felix Siauw's social experiment on Instagram related to the polemic of the use of the OnePiece flag as a protest symbol for the Indonesian youth ahead of the 80th Independence Day in August 2025. Using a qualitative method with a literature study approach and thematic content analysis, this study reveals how the principles of Islamic communication such as qaulan sadidan (correct speech), qaulan layyina (gentle speech), qaulan maysura (easy to understand speech), and qaulan kariman (noble speech) can be applied in responding to controversial popular cultural phenomena in the digital space. The results of the study show that Islamic communication ethics are able to transform controversial symbols into a constructive educational medium through moderate, dialogical, and contextual communication strategies. Felix Siauw succeeded in applying the principles of tabayyun (clarification) and wisdom (wisdom) in reducing tension while building the audience's critical awareness of the value of justice. The dynamics of public response on social media reflect the complexity of digital interactions that require an inclusive communication approach to prevent polarization and hate speech. This research confirms that Islamic communication in the digital age not only serves as a moral guide, but also as a strategic instrument for managing complex public discourse. The application of ethical principles in social media has the potential to strengthen social harmony, educate the public, and maintain the integrity of digital interactions within the framework of Islamic values, especially in the face of popular cultural phenomena that have the potential to trigger controversy.